Correlation of Knowledge and Attitude with the Use of a Travel Clinic for Pre-Travel Consultation - Ni Ketut Tannis Lestari; Putu Indah Budi Apsari; Made Indra Wijaya (WMJ (Warmadewa Medical Journal), 2023)
Utilization of tourism clinics, particularly for pre-travel consultations, remains low among domestic tourists. The current study aims to examine the relationship between knowledge level and attitude towards the utilization of tourism clinics for pre-travel consultations in Bali Province. The study sample consisted of 106 domestic tourists who were present in Bali during the period of May-September 2022. Consecutive sampling was used, and the Chi-Square Test was executed for data analysis with the aid of the SPSS version 25.0 program. The research findings indicate that the majority of domestic tourists (50%) originated from Malang. Additionally, the study revealed that women accounted for a greater proportion (62.3%) of domestic tourists. The research results also showed that 60 tourists had a good level of knowledge and utilized the tourism clinic, while 59 tourists had an agreeable attitude towards the utilization of the tourism clinic. The results of the study demonstrate a significant relationship between knowledge level (p<0.001) and attitude (p<0.001) towards the use of tourism clinics for pre-travel consultations in Bali Province. Overall, tourists have a good level of knowledge and agreeable attitude towards the utilization of tourism clinics, indicating a positive trend towards the promotion of tourism clinics for pre-travel consultations.